1983
DOI: 10.1002/neu.480140305
|View full text |Cite
|
Sign up to set email alerts
|

Possible temperature‐dependent blockage of synaptic vesicle recycling induced by a single gene mutation in drosophila

Abstract: The temperature-sensitive Drosophila mutant, shibirets1 (shi), has been shown to exhibit a reversible block in synaptic transmission at 30 degrees C. Various synaptic terminals (neuromuscular, sensory, central) of this mutant were observed by electron microscopy. At 19 degrees C, all terminals of shi showed essentially the same structural features as those of wild-type (Oregon-R) flies, while at 30 degrees C (5 or 10 min of exposure) shi terminals exhibited various structural changes not seen in the wild type.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
221
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(241 citation statements)
references
References 19 publications
20
221
0
Order By: Relevance
“…Purified dynamin also assembles into spirals or rings in the absence of membrane (5). These structures are strikingly similar to electron-dense collars that were observed many years earlier in neurons of Drosophila shibire mutants (6). Recent experiments demonstrated the ability of brain cytosol and purified dynamin to form lipid tubules (7,8) Purified dynamin can sever the lipid tubules by GTP-dependent constriction (8).…”
supporting
confidence: 57%
“…Purified dynamin also assembles into spirals or rings in the absence of membrane (5). These structures are strikingly similar to electron-dense collars that were observed many years earlier in neurons of Drosophila shibire mutants (6). Recent experiments demonstrated the ability of brain cytosol and purified dynamin to form lipid tubules (7,8) Purified dynamin can sever the lipid tubules by GTP-dependent constriction (8).…”
supporting
confidence: 57%
“…This work revealed that the basic assembly unit of dynamin, a tetramer, can polymerize into rings or spirals that resemble the collar structures seen at the necks of coated pits in the shibire mutant nerve termini (4,25). Dynamin spirals also resemble the striation pattern seen on long tubules, which originate from the plasma membrane and end in a coated pit.…”
mentioning
confidence: 74%
“…Temperature-sensitive mutations of the dynamin gene (shibire) in Drosophila cause a selective arrest of the synaptic vesicle cycle at the stage of invaginated plasmalemmal pits (3)(4)(5)(6), and transfection of dominant negative dynamin mutants in fibroblastic cells blocks clathrin-mediated endocytosis (7,8). Recent studies have shown that dynamin forms rings at the neck of invaginated clathrin-coated vesicles and suggested that a conformational change of the rings which correlates with GTP hydrolysis leads to vesicle fission (9,10).…”
mentioning
confidence: 99%